Revitalising Indigenous Rights Participation in Mining Lawmaking Process: Evaluation and Proposal for Indonesia - Nur, Asrul Ibrahim; Al Fatih, Sholahuddin; Intania, Christina Clarissa (LAW REFORM, 2024)
Indonesia's climate ambition, particularly in developing an electric vehicle ecosystem, has made significant progress since 2019 through the adoption of various legal instruments leading to mining law reform. These initiatives include establishing an electric vehicle battery industry supported by downstream mining policies. This policy ensures the availability of metal ores, such as nickel, which is a key raw material for the battery industry. However, Indigenous communities living near mining areas designated as National Strategic Projects have experienced negative impacts, including environmental damage.This study posits that environmental damage is a consequence of excluding Indigenous communities from mining policy reforms, as they traditionally serve as protectors of the environment. The primary aim of this study is to analyze the importance of Indigenous peoples’ meaningful participation and to examine the tendency of Indonesia’s mining law reforms to overlook Indigenous involvement in environmental preservation. This paper employs a doctrinal and normative approach to statutory laws.The research underscores the urgency of ensuring meaningful participation of Indigenous peoples in mining law reforms and suggests methods for restoring their right to participate through available forums and legal instruments. The paper proposes several steps to accommodate Indigenous peoples’ aspirations in legislation: first, addressing the loss of identity experienced by Indigenous peoples; second, optimizing the use of existing representative offices in each province; and third, implementing a system that allows Indigenous peoples to easily express their aspirations and complaints.